(3LGeY GdCfhGQ aj efGbH GdCNHGQs - (3YjSi Hf ehSi GdbGOQj GdfbTHfOj GdHfOfjLj , CHh GdgOj UaGA GdOjf,J (B1283 (3g` s ((3eMeO Hf NVQ Hf eMeO s)
(3ChdgG (B:s
(3CeG HYO Ef Yde GdJGQjN hGdCNHGQ eeG jfTQ HSGWg ai ebGYO Chdi GdSYGOI GdCNHGQ s
(3BNQgG (B:s
(3gPG BNQ eGJQLeJg ef cdGe GdeDdb QMeg Gddg hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B34s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B574 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B138 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdYQGbi (B(256) s
Keywords: (3GdJGQjNs